Decreased expression of Gab2 in patients with temporal lobe epilepsy and pilocarpine‐induced rat model. Issue 4 (20th December 2013) - Zhan, Ao; Xu, Xin; Chen, Ling; Wang, Xuefeng; Yanfeng, Xie; Dan, Wei; Zhan, Yan; Shi, Quanhong
ABSTRACT Growth factor receptor bound protein‐2 associated binding protein‐2 (Gab2) is widely expressed in the central nervous system, and participates in multiple signaling pathways. Recent studies showed that Gab2 was involved in the pathogenesis of Alzheimer's disease (AD). Gab2 reduces tau phosphorylation levels and is associated with cellular apoptosis and differentiation. However, whether Gab2 was also involved in the pathogenesis of epilepsy, remains unknown. This study aimed to investigate the expression pattern of Gab2 protein in brains with temporal lobe epilepsy (TLE) and in pilocarpine‐induced rat model of TLE. Western blot, immunohistochemistry, and immunofluorescence were used to assess the location and the expression level of Gab2 in the neocortex of the temporal lobe in patients with TLE and in rat model of epilepsy. Results showed that Gab2 protein was expressed mainly in the membranes and cytoplasm of neurons in the cortex and hippocampus. Gab2 protein expression was remarkably reduced in temporal neocortex of TLE patients. In hippocampus and adjacent cortex in rat epilepsy model, Gab2 expression was decreased at different time points after kindling compared with the controls, and the lowest level of Gab2 expression occurred at 1 week. Thus, significant reductions of Gab2 protein in both TLE patients and epilepsy rats suggest that Gab2 may play an important role in the pathogenesis of TLE. Synapse 68:168–177, 2014. © 2013 Wiley Periodicals, Inc.